Internal displacement and education: Overcoming barriers for learners in Kenya’s Northern Rift Valley - Caroline Adhola; Anne Ajulu-Okungu (Perspectives in Education)
Many countries face the problem of refugees and internal displacement. Internal displacement is not new to Kenya and is a recurring problem that impacts displaced children’s education. One factor affecting displacement is banditry, stemming from community fights over resources. This paper uses theoretical and conceptual arguments to explore the causes and effects of internal displacement on learning, focusing on banditry and how they can be mitigated. Fraser’s social justice theory has been used to frame this discussion. Three questions guided this inquiry: What causes internal displacement in the Northern Rift Valley of Kenya? What challenges do internally displaced learners in Northern Rift Valley face? What strategies can be used to mitigate the challenges internally displaced learners face? The paper argues for a social justice framework to address and alleviate internally displaced persons’ challenges in the North Rift Valley of Kenya.